Barriers and enablers to patient recruitment for randomised controlled trials on treatment of chronic wounds: A systematic review. Issue 6 (21st June 2018) - Bugeja, Lyndal; Low, Jac Kee; McGinnes, Rosemary A; Team, Victoria; Sinha, Sankar; Weller, Carolina
Abstract : Randomised controlled trials represent the gold standard in intervention efficacy evaluation. However, suboptimal recruitment affects completion and the power of a therapeutic trial in detecting treatment differences. We conducted a systematic review to examine the barriers and enablers to patient recruitment for randomised controlled trials on chronic wound treatment. Review registration was under PROSPERO 2017:CRD42017062438. We conducted a systematic search of Ovid MEDLINE, EBSCOhost CINAHL, Ovid Cochrane Library, Ovid EMBASE, and Ovid PsycINFO databases in June 2017 for chronic wound treatment randomised controlled trials. Twenty‐seven randomised controlled trials or qualitative studies met the inclusion criteria. Among the 24 randomised controlled trials, 21 were assessed as low quality in relation to recruitment, and 3 were assessed as high quality. All 27 studies reported barriers to recruitment in chronic wound randomised controlled trials. The reported barriers to recruitment were: study‐related, patient‐related, clinician‐related, health system‐related, and/or operational‐related. No study reported recruitment enablers. To enhance randomised controlled trial recruitment, we propose the need for improved integration of research and clinical practice. To alleviate the problems arising from inadequate reporting of randomised controlled trials, the Consolidated Standards of Reporting Trials Statement could include an additional item on recruitment barriers. This approach will allow for increased awareness of the potential barriers to recruitment for Randomised controlled trials (RCTs) in both wound management and other health care research.